'He is Our Opponent, Not Our Enemy': Two Rugby Tours and Australasian Perceptions of Japan during the 1930s. Issue 12 (13th August 2019) - Ryan, Greg
Abstract: This paper explores aspects of the Australian (1934) and New Zealand (1936) universities rugby union tours of Japan. These were conducted at a time when Australasian understandings of Japan were very limited – notwithstanding a number of very positive Japanese sporting excursions to Australia from the late 1920s. Equally this was a period when a rapidly modernizing and expansionist Japan was engendering contrasting reactions from the international community. On one hand it was a friend with whom sport provided opportunities for peace and understanding. On the other it was a threat to stability in Asia and the Pacific. Elements of this duality can be seen in both the on- and off-field conduct of the rugby tours. The unpublished private diary of one of the New Zealand players also reveals significant disjuncture with the public narrative of sportsmanship and internationalism that characterized press accounts of these and other tours.